Twelve Weeks of Aerobic Exercise at the Lactate Threshold Improves Autonomic Nervous System Function, Body Composition, and Aerobic Performance in Women with Obesity - Park, Hun-Young; Jung, Won-Sang; Kim, Jisu; Hwang, Hyejung; Lim, Kiwon (Journal of Obesity & Metabolic Syndrome, 2020)
The present study examined the effects of a prolonged exercise intervention at the lactate threshold (LT) on body composition, aerobic performance, and the autonomic nervous system (ANS) in women with obesity. A total of 36 obese Korean women aged 36 to 55 years (mean±standard deviation, 44.8±5.2 years) were randomly assigned to a control group (CON, n=18) or an experimental group (EXP, n=18); and EXP underwent aerobic exercise training three times a week at a heart rate corresponding to the LT (HR_LT) for 12 weeks. All dependent variables (body composition, aerobic performance, and ANS function parameters) were evaluated before and after training. Compared with the CON group, the EXP group showed significant improvement in body composition (body weight, -4.57 vs. -2.40 kg; body mass index, -1.79 vs. -0.96 kg/m ; %body fat, -4.63 vs. -1.41; fat-free mass, 3.24 vs. -0.08 kg), aerobic performance (oxygen consumption at LT, 5.74 vs. 0.12 mL/kg/min; maximal oxygen consumption, 5.41 vs. 2.14 mL/kg/min; treadmill speed at HR_LT, 1.40 vs. 0.29 km/hr; bicycle load at HR_LT, 18.62 vs. 4.52 w; and ANS function (mean RR, 50.83 vs. -15.04 ms; standard deviation of NN intervals, 5.08 vs. -0.55 ms; root mean square of successive differences, 6.42 vs. 1.87 ms; total power, 0.34 vs. 0.10 ms ; high frequency, 0.32 vs. -0.04 ms ; low frequency/high frequency, -0.09 vs. 0.01). Aerobic exercise at the LT for 12 weeks is a practical method of improving body composition, aerobic performance, and ANS function for women with obesity.